Re-description of Azygokeras columbiae Koeller & Littlepage, 1976 (Calanoida: Aetideidae) and musculature of the male grasping antennule - Bradford-Grieve, Janet M.; Boxshall, Geoffrey A. (Zootaxa, 2019)
Azygokeras columbiae from Bute Inlet, British Columbia, Canada, is re-described, correcting some details and adding information not available in the original description. Azygokeras columbiae is unique amongst male Aetideidae in having the right antennule modified for grasping but without a true knee joint (geniculation) between segments XX and XXI nor a hiatus in the musculature at this joint, typical of taxa with a geniculate male antennule. Male Azygokeras have wide pivot points and arthrodial membranes between segments XXI and XXII, XXIII and XXIV and XXV and XXVI that allow greater movement in several planes than in homologous segments of Euaugaptilus and Heterorhabdus. Modifications of the terminal antennular joints allow for extensive movement in several planes associated with a series of short muscles in segments XIX to XXVI. These muscles become progressively more massive from proximal to distal on the antennule and are paired with an antagonistic muscle also increasing in mass distally.